Microencapsulation of Ruellia tuberosa L. Extracts Using Alginate: Preparation, Biological Activities, and Release - Andriana Kusuma Pertiwi; Choirin Annisa; Zubaidah Ningsih; Anna Safitri (Universitas Gadjah Mada, 2023)
The bioactive compounds naturally present in plants have great importance due to their biological characteristics. These substances could lose their active characteristics since they are highly unstable. Microencapsulation is one of the techniques to improve stability and protect these compounds. In this work, Ruellia tuberosa L. ethanolic extracts microcapsules were prepared using a freeze-drying method by varying pH, alginate concentration, and stirring time. The encapsulation efficiency (EE), characteristics, alpha-amylase inhibition activity, and release behavior of the microcapsules were investigated. The results highlighted that the highest encapsulation efficiency for the microcapsules was obtained at pH 6, alginate concentration of 1% (w/v), and 30 min of stirring time (51.63% EE). The microcapsules mostly had spherical shapes with a mean diameter of 197.53 μm. The alpha-amylase inhibition assay from microcapsules resulted in the IC50 value of 46.66 ± 0.13 μg/mL, demonstrating high biological activity. The bioactive substances from microcapsules were released during intervals of 30–120 min at pH values of 1.2 and 7.4. Only 3.51% of the bioactive substances were released at pH 1.2 after 120 min, compared to 55.78% at pH 7.4. Overall, this work confirms the possibility of developing plant extracts with preserved biological activity using the produced microcapsules.